A borane-mediated palladium-catalyzed reductive allylic alkylation of α, β-unsaturated carbonyl compounds. Issue 8 (21st January 2020) - Trost, Barry M.; Zuo, Zhijun; Schultz, Johnathan E.; Anugula, Nagaraju; Carr, Katherine A.
Abstract : A palladium-catalyzed allylation of ester-derived boron enolates, which is prepared through 1, 4-reduction of α, β-unsaturated ester analogues. Abstract : The development of the palladium-catalyzed allylic alkylation of in situ generated boron enolates via tandem 1, 4-hydroboration is reported. Investigation of the reaction revealed insights into specific catalyst electronic features as well as a profound leaving group effect that proved crucial for achieving efficient allylic alkylation of ester enolates at room temperature and ultimately a highly preparatively useful synthesis of notoriously challenging acyclic all-carbon quaternary stereocenters. The method demonstrates boron enolates as viable pro-nucleophiles in transition-metal catalyzed allylic alkylation, potentially opening up further transformations outside their traditional use.